Coordinated charging of EV fleets in community parking lots to maximize benefits using a three-stage energy management system - Isha Chandra; Navneet Kumar Singh; Paulson Samuel; Mohit Bajaj; Ievgen Zaitsev (Scientific Reports)
Abstract The rapid global adoption of electric vehicles (EVs) necessitates the development of advanced EV charging infrastructure to meet rising energy demands. In particular, community parking lots (CPLs) offer significant opportunities for coordinating EVs’ charging. By integrating energy storage systems (ESSs), renewable energy sources (RESs), and building prosumers, substantial reductions in peak load and electricity costs can be achieved, while simultaneously promoting environmental sustainability. This paper presents a novel three-stage real-time Energy Management System (EMS) designed to coordinate EV charging in CPLs, integrating solar photovoltaics, wind energy, ESSs, and building backup units. The proposed EMS operates in three stages: (1) day-ahead scheduling of energy generation and consumption, (2) real-time power management to address deviations between forecasted and actual power generation and demand, and (3) priority-based EV charging, which considers EV state of charge (SOC) and owner preferences. The system is evaluated through MATLAB® simulations under four different scenarios and based on six performance indices: daily electricity bills, cost savings, self-sufficiency, self-consumption, carbon emissions, and fairness in EV charging. The results demonstrate that the proposed EMS can reduce electricity bills for parking lot operators (PLOs) by up to 45%, with a corresponding decrease in carbon emissions by 40% compared to uncoordinated charging scenarios. Additionally, the EMS improves the self-sufficiency ratio by up to 75% and increases the self-consumption ratio to 85%. The system also ensures fairness in charging, achieving a fairness index of 0.82, thus addressing the needs of both PLOs and EV owners. This research underscores the potential of CPLs to optimize energy use, lower costs, and contribute to broader sustainability goals by integrating renewable energy and intelligent charging strategies.